Aquaporins and their function in root water transport under salt stress conditions in Eutrema salsugineum. (October 2019) - Qin, Shenghao; Liu, Yiyang; Han, Yan; Xu, Guoxin; Wan, Shubo; Cui, Feng; Li, Guowei
Highlights: The root hydraulic conductivity of E. salsugineum was repressed by salt stress. However, propionic acid, usually used as an aquaporin inhibitor, conversely enhanced the root hydraulic conductivity of E. salsugineum . The aquaporin family was characterized and two EsPIPs were identified to play a role in salt stress. Abstract: Eutrema salsugineum is considered as extremophile model species. To gain insights into the root hydraulic conductivity and the role played by aquaporins in E. salsugineum, we investigated the aquaporin family profiles, plant water status and root hydraulic conductivity under standard (salt-free) and salt stress conditions. We found that there was no variation in the relative electric conductivity of the leaves when the salt concentration was less than 200 mM NaCl, and the transpiration rate dropped to 60.6% at 100 mM NaCl for 14 days compared to that at standard conditions. The pressure chamber techniques indicated that the root hydraulic conductivity of E. salsugineum was repressed by salt stress. However, propionic acid, usually used as an aquaporin inhibitor, unexpectedly enhanced the root hydraulic conductivity of E. salsugineum . The aquaporin family in E. salsugineum was profiled and the PIP aquaporin expression was investigated at the transcriptional and translational levels. Finally, two EsPIPs were identified to play a role in salt stress. The overall study provides evidence on how halophytes maintain their water status and aquaporin regulation pattern under salt stress conditions.